Do Plant Inspections Predict Future Quality? The Role of Investigator Experience - Ball, George; Siemsen, Enno; Shah, Rachna (Manufacturing and Service Operations Management, 2017)
Plant inspections enable firms to manage their quality risk in global supply chains. However, surprisingly little research examines the relationship between such inspections and future product quality. In this paper, we study how well plant inspection outcomes predict the hazard of a future recall and analyze how investigator experience affects this predictive relationship. Using secondary data spanning a seven-year period in the medical device industry and a recurrent-event Cox proportional hazard model, our analysis shows that inspection outcomes reliably predict future product recalls. However, inspection outcomes become an unreliable predictor of recalls with an increase in site-specific investigator experience. Through post hoc analysis, we also show that the hazard of a recall at a plant increases with site-specific experience, independent of the inspection outcome. Compared to the first visit by an investigator, the recall hazard increases by 21% the second time the investigator visits a specific plant, and by 57% on the third visit. We propose investigator rotation and investigator sequencing as two policies to help mitigate this increased recall risk. The online appendix is available at https://doi.org/10.1287/msom.2017.0661 .